Performance of ZnS and ZnSe Doped on Cu2+ for Photovoltaic Devices - Thuy, Le Xuan; Thanh Tung, Ha; Dat, Le Tien; Le Minh Nhan (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
This study utilizes passive ZnS@Cu2+ and ZnSe@Cu2+ layers deposited on the CdS and CdSe quantum dots to reduce dark current and enhance photon absorption. The films were fabricated utilizing the successive ionic layer adsorption and reaction technique with an optimized and suitable Cu/Zn doping ratio. Ultraviolet–visible spectroscopy, X-ray diffraction, and field emission scanning electron microscopy analyses indicate a change in the absorption edge within the visible light region when ZnS and ZnSe are doped with Cu2+ ions. Power conversion efficiency measurements reveal that the ZnSe@Cu2+ photoelectrode increases the current density (JSC 23 mA.cm-2) compared to ZnS@Cu2+ The photoelectrode exhibits a short-circuit current density (JSC ≈ 22 mA · cm−2), leading to improved conversion efficiency. It also shows the lowest charge transfer resistance (Rct2 = 33 − Ω), indicating efficient interfacial kinetics in the photoelectrode suggests more efficient electron transport and reduced recombination.